KAJIAN BENTUK DAN MAKNA PADA LOGO DESA VISESA: Study of The Form and Meaning of The Desa Visesa Logo - Made Gana Hartadi (Jurnal Dimensi Seni Rupa dan Desain, 2024)
Desa Visesa is accommodation and a tourist destination that applies traditional Balinese permaculture into a modern package with the Panca Visesa concept. The implementation of the concept is carried out thoroughly and harmoniously between local residents, companies and tourists. The logo is designed based on the company concept. This research examines the form of illustrations and letters in the Desa Visesa logo based on the meaning of denotation and connotation, thereby revealing the effectiveness of the logo. The research method is descriptive qualitative with an interpretive approach. The illustration is composed by geometric, natural and abstract, but not yet able to reflect the kayon. Letters are composed of several types of letter anatomy. The connotation meanings are able to represent the values ​​of Panca Visesa. The effectiveness of the logo hasn’t been optimal because it isn’t able to describe the company in its entirety.